Efikasi Pupuk Organik dan Pupuk Anorganik terhadap Pertumbuhan dan Produksi Tanaman Padi di Lahan Kering. - Yakup, Yakup; Simamora, Markus William Kaisar; Azzahra Jenyca, Zsa-Zsa; Sholehah, Nur; Hunafa, Gatmir Zaki; Laoli, Jaeristia (Seminar Nasional Lahan Suboptimal, 2024)
Yakup, Y., Simamora, W. K. S., Jenyca, Z. A., Sholehah, N., Hunafa, G. Z., Laoli, J. (2024). Efficacy of organic fertilizers and inorganic fertilizers on the growth and production of rice plants in dry land. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-12 Tahun 2024, Palembang 21 Oktober 2024. (pp. 461–476).  Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Growing rice plants in dry land faces significant challenges such as lack of water and low soil fertility. Unbalanced fertilization is also a factor that causes a decrease in rice productivity. This research aimed to determine the effect of applying organic fertilizer (NAP and NS) at various doses of inorganic fertilizer (N, P, and K) on the growth and production of rice plants in dry land.  Held from February 2007 to June 2007 at Agro Techno Park, Bakung Village, North Inderalaya District, Ogan Ilir Regency, South Sumatra.The method used was a factorial randomized block design with two factors and each treatment was repeated three times.  The first factor is the provision of organic fertilizer, namely: control (P0), NAP organic fertilizer (P1) and NS organic fertilizer (P2).  The second factor is the dose of inorganic fertilizer (N, P, K), namely: control (A0), 25% inorganic fertilizer (A1), 50% inorganic fertilizer (A2), 75% inorganic fertilizer (A3), 100% inorganic fertilizer (A4 ). Inorganic fertilizer treatment had a significant effect on the number of productive tillers. The treatment of organic fertilizer (P), inorganic fertilizer (A), and the interaction of organic fertilizer and inorganic fertilizer (PxA) had no significant effect on plant height, maximum number of tillers, number of productive tillers, number of fruity panicles, number of empty panicles, percentage of empty grains, percentage of grain content, weight of 1000 grains, number of grains per panicle, dry grain weight, dry straw weight and yield per ha.  Grain production in the NAP organic fertilizer treatment with a 75% inorganic fertilizer dose (P1A3) was 2.78 tons per ha, while grain production in the NS organic fertilizer treatment with a 100% inorganic fertilizer dose (P2A4) was 2.45 tons per ha.  Grain yield in the P1A3 treatment increased by 13.46%, while grain yield in the P2A4 treatment increased by 5.71%. Organic Fertilizer plays a role in making the use of inorganic fertilizer efficient. The use of organic fertilizer is not to replace inorganic fertilizer, but is used as a complement to increase soil and plant productivity in a sustainable manner. Therefore, it is best to use a combination of organic fertilizers in rice cultivation. Further research needs to be carried out on different varieties, for example on tidal rice or lowland swamp.